2015
DOI: 10.1007/s10151-015-1311-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Crohn’s disease-related high perianal fistulas combining the mucosa advancement flap with platelet-rich plasma: a pilot study

Abstract: BackgroundHealing rates after surgical closure for high perianal fistula in patients with Crohn’s disease are even more disappointing than in patients with cryptoglandular fistulas. The objective was to improve healing rates by combining the well-known mucosal advancement flap with platelet-rich plasma.MethodsA prospective pilot study was conducted in one tertiary referral centre. Consecutive patients with primary or recurrent Crohn’s disease-related high perianal fistulas, defined as involving the middle and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
(24 reference statements)
1
28
0
1
Order By: Relevance
“…The remaining studies (16,17) are to demonstrate the closure of upper perianal fistulas with a technique combining advancement flaps and platelet-rich plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies (16,17) are to demonstrate the closure of upper perianal fistulas with a technique combining advancement flaps and platelet-rich plasma.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…An augmented approach was used in a pilot trial16. This involved placement of a seton, followed by local treatment with platelet‐rich plasma and mucosal advancement flap.…”
Section: Resultsmentioning
confidence: 99%
“…This study evaluated a small cohort of patients with PCD who were treated with endorectal advancement flaps or MAFs; for patients with ileal pouches, ASCs and PRP yielded satisfactory long‐term outcomes. Although several studies have assessed anorectal fistulas treated with ASCs or PRP , both cryptoglandular and PCD‐associated, this is the first study to combine both techniques added to the creation of an endorectal advancement flap or MAF.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have assessed anorectal fistulas treated with ASCs or PRP [9,10,[17][18][19][20][21][22][26][27][28][29][30], both cryptoglandular and PCD-associated, this is the first study to combine both techniques added to Historically, fistulotomy has been the main treatment for transsphincteric fistulas; however, incontinence was a major disadvantage [31]. Therefore, new surgical techniques, such as the MAF, were developed [31].…”
Section: Discussionmentioning
confidence: 99%